A new dimension of success in the management of airway disease in children with neurological deficit. (December 2020) - Kokje, Vivianne Beatrix Christina; Mermod, Maxime; Bertinazzi, Martina; Sandu, K.
Abstract: Objectives: Anomalies of the larynx and trachea can cause respiratory distress in infants and older children. Depending on its nature, degree and extent of the disease invasive open surgery is indicated. Non-airway-related co-morbidities increase the challenges in its treatment. Neurological deficit poses a great challenge as it is associated with hypotonia and causes diminished laryngeal coordination. The definition of success in treatment of laryngotracheal disease has always focused on the post-operative functional outcomes: breathing, voice swallowing. The aim of this study is to describe a new dimension of success in the management of laryngotracheal disease in children with moderate neurological deficit, where the expected functional gain is less than in otherwise healthy children. Methods: This retrospective observational study includes all patients who have undergone open reconstructive airway surgery between 2012 and 2017. Control patients without neurological deficit and cases with moderate neurological deficit were included. Functional outcome data was obtained from clinical records and two questionnaires were filled in by the parents of the children: one the pediatric voice-handicap index (pVHI) and a quality of life questionnaire. Results: Thirty-two children were included of which ten had moderate neurological deficit. Both groups revealed post-operatively an improvement in the functional outcomes: breathing, voice and swallowing, however, as expected, a trend was observed towards less functional improvement in children with neurological deficit. Both groups reveal a remarkable gain in quality of life (QoL). Conclusion: Indicating the QoL to be an unidentified, dimension of success in the management of laryngotracheal disease in children with moderate neurological deficit.